Bullous disorders of the newborn. - Bonifazi, E. (European Journal of Pediatric Dermatology, 1997)
The blister is a cavity full of fluid which protrudes on the skin. The layman calls blister even the white wheal of urticaria which is not a cavity. The latter is deeper and spontaneously regresses in a few minutes without any residua. However, the mistake of the layman is partially justified by the etymology, because pomphus and pemphigus, which is the most common autoimmune bullous disorder, have the same root. The blister is larger than the vesicle and can be easily seen. On the other hand, the vesicle is rarely visible, except for particular cases and sites. (...).